Effect of Bi doping on the thermoelectric properties of Mg2Si0.3Ge0.04Sn0.66 compound - Jia Ju (Journal of Materials Research and Technology, 2022)
N-type Bi-doped Mg2(Si0.3Ge0.04Sn0.66)1-xBix (0<x≤0.03) compounds were successfully fabricated by solid state reaction-spark plasma sintering (SPS). The XRD results indicate that all prepared samples are nearly phase pure Bi-doped solid solutions. The lattice constant and the electrical conductivity of the samples increases while the Seebeck coefficient decreases with the increase of the doped Bi content. The figure of merit (ZT) decreases at a low temperature but increases at a high temperature while increasing the Bi content. At the temperature of 800K, ZT value at x = 0.03 is about 1.3, comparing to 1.1 for x = 0.01.